Peranan Evaluasi Pembelajaran Berbasis Web Kahoot - Muhammad Fauzil Azim; Nadila Ramadani; Zulfani Sesmiarni (KOLONI, 2025)
This study aims to analyze the role of web-based learning evaluation using Kahoot as an innovation to enhance evaluation quality in the digital era. Technological transformation requires teachers to implement evaluation methods that are more interactive and efficient compared to traditional evaluations, which tend to be monotonous and less engaging. Kahoot, as a web-based evaluation platform, offers an interactive quiz model with gamification elements that can improve students’ motivation, participation, and engagement. This research employs a literature review method by examining journal articles, books, proceedings, and research reports published within the last five years. The analysis was conducted using a content analysis approach to produce theoretical synthesis regarding the effectiveness, benefits, and challenges of using Kahoot in learning evaluation. The findings indicate that Kahoot plays a significant role in supporting more engaging learning evaluations through game mechanics, leaderboards, immediate feedback, and dynamic visual displays. The platform also assists teachers in improving evaluation efficiency by providing automatic and real-time results. However, Kahoot presents several limitations, such as dependence on stable internet connectivity, the need for adequate devices, limited types of questions, and the necessity of training for both teachers and students. Despite these challenges, Kahoot’s potential as an evaluation tool remains high due to its ability to enhance students’ cognitive, affective, and psychomotor domains. Therefore, integrating Kahoot into learning evaluation can be an effective strategy to foster more innovative learning processes aligned with the needs of 21st-century education.